Why do we all want to be young and beautiful (and women especially)? From the evolutionary psychological perspective - Tadinac, Meri (Array, 2010)
Within social sciences, the standards of beauty were for a long time considered to be culturally determined, meaning that different people with different life experiences in different cultures acquire different standards of beauty, as captured in the famous sentence “Beauty is in the eye of the beholder”. However, two groups of findings have challenged this common assumption: first, people in different cultures generally agree on which faces are attractive ; second, preferences emerge early in life, before cultural standards of beauty are likely to be assimilated. Evolutionary psychology explores the psychological adaptations (evolved psychological mechanisms constructed by natural selection) that constitute human nature. From the perspective of evolutionary psychology, beauty is not a cultural construct and appreciating beauty is not learned but is rather a biological adaptation, a part of universal human nature: the preferences for some physical characteristics reflect adaptations for mate choice because they signal aspects of mate quality. Theory of natural selection explains the adaptations, which help organisms in their tasks of survival. However, an organism can be adapted and survive for many years without passing its qualities to future generations – to pass them it must reproduce. The theory of sexual selection explains the adaptations that have arisen as a consequence of successful mating. In order to gain reproductive success, women and men adopt certain mate selection strategies – integrated sets of adaptations, not necessarily conscious, which organize and guide the individual’s reproductive efforts.